Chronic Infection of the Prostate by Chlamydia muridarum Is Accompanied by Local Inflammation and Pelvic Pain Development. Issue 5 (17th January 2017) - Sanchez, Leonardo R.; Breser, Maria L.; Godoy, Gloria J.; Salazar, Florencia C.; Mackern‐Oberti, Juan P.; Cuffini, Cecilia; Motrich, Ruben D.; Rivero, Virginia E.
Abstract : BACKGROUND: Chlamydia trachomatis urogenital infections are the leading cause of sexually transmitted bacterial infections. Although the prevalence of chlamydial infection is similar in men and women, current research is mainly focused on women, neglecting the study of male genital tract infections. We, therefore, investigated Chlamydia infection in the rodent male genital tract. MATERIALS AND METHODS: Male NOD and C57BL/6 mice were inoculated in the meatus urethra with C. muridarum . Bacterial DNA, leukocyte infiltration of male genital tract tissues, pelvic pain, and Chlamydia ‐specific immune responses were analyzed at different time points. RESULTS AND CONCLUSIONS: The inoculation of C. muridarum in the meatus urethra of male mice resulted in an ascending and widely disseminated infection of the male genital tract. C. muridarum remained longer and with the highest bacterial burdens in the prostate, thus showing a special tropism for this organ. Infection caused leukocyte infiltration, mainly composed by neutrophils, and also induced early pelvic pain development that rapidly dropped and resolved as the infection became chronic. Bacterial load and leukocyte infiltration was observed in all prostate lobes, although dorsolateral prostate was the most affected lobe. Interestingly, immune responses induced by both mice strains were characterized by the production of high levels of IL‐10 during early stages of the infection, with highest and sustained levels observed in NOD mice, which showed to be less efficient in clearing the infection. Chronic infection of the prostate accompanied by local inflammation and pelvic pain development described herein have important implications for the improvement of the diagnosis and for the design of new efficient therapies. Prostate 77:517–529, 2017 . © 2017 Wiley Periodicals, Inc.